9(2-3x)-29=8x-(x-25)

Simple and best practice solution for 9(2-3x)-29=8x-(x-25) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9(2-3x)-29=8x-(x-25) equation:



9(2-3x)-29=8x-(x-25)
We move all terms to the left:
9(2-3x)-29-(8x-(x-25))=0
We add all the numbers together, and all the variables
9(-3x+2)-(8x-(x-25))-29=0
We multiply parentheses
-27x-(8x-(x-25))+18-29=0
We calculate terms in parentheses: -(8x-(x-25)), so:
8x-(x-25)
We get rid of parentheses
8x-x+25
We add all the numbers together, and all the variables
7x+25
Back to the equation:
-(7x+25)
We add all the numbers together, and all the variables
-27x-(7x+25)-11=0
We get rid of parentheses
-27x-7x-25-11=0
We add all the numbers together, and all the variables
-34x-36=0
We move all terms containing x to the left, all other terms to the right
-34x=36
x=36/-34
x=-1+1/17

See similar equations:

| 4(3x-7)=6x-4 | | -4.3g=|25.8 | | -10g-8=42 | | 6r-9+5r=10r-2 | | 3.95+8.95b=47.65, | | 3.95m+8.95=47.65, | | 10+6s=4s-6 | | 3x+18−5=27 | | 26-5x=8x+6(-8+4x) | | 7(3y+6)+(-24)=0 | | 3r+10=2r-200 | | x-1/5=x-(2x-6)/5 | | 3x−5=19+(x+8) | | 3x+18−15=27 | | 3b=3.24 | | -2(5-6k)=86 | | 2×18x=6+7x | | -3g+5=-4g | | 3(x-5)+2x=4(x-4+x+1 | | 1/8=k+8/9 | | 2.18x=6+7x | | 3x+3+3x-1=3x+8 | | 6b+10=-4+8b | | 17(2w-15)+2=246.2 | | -3k-6k=-2-6k | | 7x-10+9x-11=110 | | 9x-2+3x=118 | | 7x-10+9x-11=45 | | 5q=6+3q | | 15x+15=7x+2+10x-13 | | 6j+2=7j | | 6x-25=45-x |

Equations solver categories